Comparative and population genomics of secondarily temperate Paranotothenia angustata, New Zealand black cod - Rayamajhi, Niraj (2024)
Notothenioids are a group of teleost fish that have undergone at least two thermal transitions in their evolutionary history. Due to paleo-geological, -climatic, and -oceanographic changes, the environment of Antarctica transitioned from temperate to cold. Antifreeze glycoproteins became a key evolutionary innovation that enabled a group of temperate, bottom-dwelling notothenioids to adapt to increasingly cold waters. With the availability of vacant ecological niches, the cold-resistant notothenioids diversified over evolutionary time. Most of these derived lineages became cold-specialized (e.g., Trematomus borchgrevinki). Remarkably, a few of them readapted to a warmer environment, becoming secondarily temperate (e.g., Paranotothenia angustata); however, the genetic architecture of readaptation for these organisms remains largely unknown. In this dissertation, my first goal was to identify the optimal de novo genome assembly strategy for notothenioids, as robust assembly is required for genome-based projects (Chapter 2). I evaluated Illumina-, Nanopore-, and PacBio-based genome assembly strategies with T. borchgrevinki. My results suggest that the strategy based on long-reads only is the current best approach and can be optimized through a subsampling method. My results indicate that short-reads only and hybrid (short- and long-reads) based strategies produce low quality assemblies. My second goal was to identify genomic features associated with secondarily temperate adaptations of P. angustata (Chapter 3). My results suggest that I have produced high quality chromosome-level assemblies for P. angustata (a focal species) and T. borchgrevinki (an outgroup). They also indicate that the genome of P. angustata consists of lineage-specific DNA transposons, chromosomal fusion patterns, inversions (most of which co-localized with one to three protein-coding genes having signals of accelerated molecular evolution), and translocations. This line of evidence calls for a detailed future investigation on the role of ...